2011
DOI: 10.1186/1471-2156-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of polymorphisms in candidate genes and the QTL region on chicken age at first egg

Abstract: BackgroundThe age at first egg (AFE), an important indicator for sexual maturation in female chickens, is controlled by polygenes. Based on our knowledge of reproductive physiology, 6 genes including gonadotrophin releasing hormone-I (GnRH-I), neuropeptide Y (NPY), dopamine D2 receptor (DRD2), vasoactive intestinal polypeptide (VIP), VIP receptor-1 (VIPR-1), and prolactin (PRL), were selected as candidates for influencing AFE. Additionally, the region between ADL0201 and MCW0241 of chromosome Z was chosen as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 51 publications
(45 reference statements)
4
25
0
1
Order By: Relevance
“…In the 2 INDEL variants, genotypic frequencies of VIP/VspI mutation did not follow the Hardy-Weinberg law (P<0.05) and comparable results were also found in other chicken populations. For example, on Ningdu Shanghuang breed, the frequency of C allele was higher than T allele in DRD2/BSeGI mutation point (Xu et al, 2010;Xu et al, 2011a;Xu et al, 2011b). In addition, Kim et al (2004) showed that C allele frequency (0.31) was lower than T allele (0.69) at IGF-I/PstI polymorphic position in Ogol chicken, but on the same Madandaran chicken, the distribution of 2 alleles was relatively equal (0.51 and 0.49) (Abbasi & Kazemi, 2011).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the 2 INDEL variants, genotypic frequencies of VIP/VspI mutation did not follow the Hardy-Weinberg law (P<0.05) and comparable results were also found in other chicken populations. For example, on Ningdu Shanghuang breed, the frequency of C allele was higher than T allele in DRD2/BSeGI mutation point (Xu et al, 2010;Xu et al, 2011a;Xu et al, 2011b). In addition, Kim et al (2004) showed that C allele frequency (0.31) was lower than T allele (0.69) at IGF-I/PstI polymorphic position in Ogol chicken, but on the same Madandaran chicken, the distribution of 2 alleles was relatively equal (0.51 and 0.49) (Abbasi & Kazemi, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…Enhancing and stabilizing breeding quality are one of the methods used to improve these indicators. Many candidate genes associated with poultry productivity have been identified (Abdi et al, 2014;Fatemi et al, 2012;Xu et al, 2011a;Xu et al, 2011b), as a result of the unprecedented improvements of genetic technology, especially molecular genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turkeys, two spliced isoforms were isolated and some studies suggested that the expression of the DRD2 mRNA was correlated with broodiness (Schnell et al, 1999). In chickens, studies indicated that the polymorphisms of DRD2 gene exhibited a significant association with chicken egg number at 300 days of age (Xu et al, 2011b), the age at first egg (Xu et al, 2011c), and broody frequency and duration of broodiness (Xu et al, 2010). Both of these studies suggested that DRD2 gene played a critical role on regulating the reproductive traits of avians.…”
Section: Discussionmentioning
confidence: 99%
“…Su trascendencia radica en que la puesta del primer huevo marca el inicio de la vida productiva o reproductiva, dependiendo del destino posterior que se le dé al huevo. En la gallina, al igual que en otras especies, la maduración sexual es consecuencia de una compleja cascada de eventos vinculados con el eje hipotálamohipófisis-gonadal (Xu et al, 2011), dependiente de la edad y el peso corporal (Brody et al, 1984) y de la composición corporal, incluyendo esta última tanto el contenido de grasa corporal (Bornstein et al, 1984) como el contenido del cuerpo libre de grasa o tejido magro (Soller et al, 1984). A su vez, la importancia del peso corporal y de la edad en relación con la madurez sexual cambia de acuerdo al régimen de alimentación.…”
Section: Introductionunclassified